The students' language attitudes towards lecturers' code mixing: An SFL study - Manar, Marsandi; Purwaningrum, Prapti Wigati (JEES (Journal of English Educators Society), 2021)
As the effort to have the insight into the existing status of a local language in Indonesia especially in the academic setting viewed as the respected discourse, this current study aims to delineate the attitudes of millennial students towards lecturer’s code mixing to Sundanese during courses. 42 responses reflecting respondents’ perspectives towards the issue were collected via qualitative questionnaire. To reveal the view of participants on the issue under the context of higher education, responses in the forms of 62 clauses were analysed by the transitivity framework of Halliday and Matthiessen. The findings of this SFL study shows that lecturer’s code mixing to Sundanese during courses were viewed by 74% of Sundanese and non-Sundanese participants in positive ways while the rest addressed it with negative attitude. The positive attitudes were respectively represented in material, mental, relational, and existential processes while the negative attitudes were constructed sequentially in relational, material and mental, verbal, and existential clauses. The main reasons in the positive attitudes as revealed by the transitivity analysis are associated with the needs to maintain and preserve local language especially Sundanese via the academic channel. HIGHLIGHTS: The processes of meaning making in positive-attitude responses are realized especially in material clauses to establish the importance of preserving local languages especially Sundanese through the academic channel. The processes of meaning making in negative-attitude responses are realized especially in relational clauses to give priority to the negative impact of using Sundanese on the academic aspect especially for non-Sundanese students. The academic setting viewed as the respected world can be a medium for the co -existence of national, international, and local languages